If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7y=6(y+10)
We simplify the equation to the form, which is simple to understand
7y=6(y+10)
Reorder the terms in parentheses
7y=+(+6y+60)
Remove unnecessary parentheses
+7y=+6y+60
We move all terms containing y to the left and all other terms to the right.
+7y-6y=+60
We simplify left and right side of the equation.
+1y=+60
We divide both sides of the equation by 1 to get y.
y=60
| x+x+2+3x=57 | | [x-5]=-9 | | -(4y+3z-2)= | | [x-5]=9 | | 96=-3(-5x-7) | | 6--7=3x+8-2x | | -2+11=15x-4-14x | | x+3(x-4)=-72 | | (x+10)*(x+10)=9 | | -8-2x=-7-7x | | -4-6=12-10x | | -99=-3(-7x-2) | | 6x+4x=200 | | -6.5+x=12.25 | | 6g-6-3-6g= | | -3y-12=5y+44 | | 12(n+7)=4(21+3n) | | y=3x^2(x^2) | | [4x-20]+5=12 | | 7x-(2+4x)= | | .3x-.06x=1.25 | | 4p+4q=40 | | -280=7(-5x-5) | | 271-5x=40x+21 | | 5n-4(5n-5)=50 | | 4(2x-7)=8-x | | 2=-(5x-7) | | 252=6(5x+7) | | 5a-(4)=21 | | 7(y+8)=9y+56 | | 5x+36=14x-45 | | 32=-81(1-5x) |